Leadership in Africa: A hermeneutic dialogue with Kwame Nkrumah and Julius Nyerere on equality and human development - Häussler, Karl-Peter (Department of Social Development, 2018)
This study deals with leadership and 'humanness' and compares the perceptions of human equality of two outstanding African leaders, 'fathers of their nations', Kwame Nkrumah, first president of Ghana, and Julius Nyerere, first president of Tanganyika, later Tanzania. Leadership is a key issue for political, economic and social development in Africa and worldwide. This is especially true in times of financial and economic globalisation that affects people in poor African countries significantly. Half a century after the independence of most countries on the continent, poverty is the daily experience of the majority of Africa's people. Public criticism about the present political leadership and their 'delivery' of goods and services to the people is widespread and profound. This problem prompted me to study the leadership experiences of Nkrumah and Nyerere. The overall goal of this research is to better understand Nkrumah and Nyerere as leaders in Africa. Therefore, my study has two research questions: what are their perceptions on equality and human development - and what is their historical and contemporary relevance, in times of human rights violations and increasing inequalities. The methodological choice is critical hermeneutics (Gadamer 1990, 2013; Ricoeur 1991b; Habermas 1992b, 1996), which allows a multi-cultural historical and contemporary dialogue with Nkrumah and Nyerere through their text. Hermeneutics also has relevance in Africa (Oruka 1990; Serequeberhan 1994; Mbembe 2001). I name my method the "triple jump" (Häussler 2009a). The study is a combination of a quantitative and a qualitative method with a hermeneutic conversation. The core-keywords of the dialogues are colonialism, unity, socialism, equality, freedom and development. There are three significant findings that contribute new knowledge to our understanding of Nkrumah and Nyerere as leaders. First, that using the hermeneutic dialogue (my "triple jump") as a holistic and practical model enables a 'better' understanding of Nkrumah and Nyerere. Second, interpreting their perceptions on human equality reveals that both leaders prioritise education as a critical part of human development and achieving equality in society. It also unveils differences in their focus: Nkrumah on de-colonisation and African unity; Nyerere on social and economic self-reliance, and equal rights. Thirdly, the study reveals tensions between their discourses on equality and freedom and their personal capacity to deal with power, opposition, human rights and idealism. My study concludes with recommendations for the development of ethical leadership and for personal support for leaders in office.